Antifungal Activity of Lactic Acid Bacteria Isolated from Soil Rhizosphere on Fusarium Species Infected Chilli Seeds - Akaram Husain; Zaiton Hassan; Mohd Nizam Lani; Nur Huda Faujan (Global Society of Scientific Research and Researchers, 2024)
Non-Indexed Publication